Using child rights education to infuse a social justice framework into universal programming. (February 2020) - Naser, Shereen C; Verlenden, Jorge; Arora, Prerna G; Nastasi, Bonnie; Braun, Lindsay; Smith, Rokeishia
A key part of promoting social justice as school psychologists is infusing practice with actions that breakdown systems of inequity and incorporate systems of inclusion. The current manuscript provides a description of applying social justice as a framework in universal programming through child rights education. Additionally, the manuscript describes the use of action research methodology to incorporate a social justice perspective not only in program content but also in program development. Results of this project provide preliminary support for child rights education in impacting student's knowledge regarding child rights, teacher acceptability of such programming, and modest impact on social and emotional skills related to interpersonal relationships in the classroom.